THE ROLE AND CHARACTERISTICS OF INNOVATIVE MANAGEMENT IN THE EDUCATIONAL SYSTEM IN UZBEKISTAN - Saidova Xilolaxon Rashidjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the tasks of innovative management methods and the issues of organizing innovative activities are described. In particular, the role of innovative activities in education in Uzbekistan and the issues of organizing innovative activities in the educational system are discussed in detail.